Individual and Group Extension Methods: Perspectives from Vi-Agroforestry Project in Masaka district, central Uganda - Buyinza, Mukadasi; Bukenya, Mohamed; Bbale, Willey; Ndemere, Peter (Makerere Journal of Higher Education, 2009)
A study was conducted to assess the effectiveness of group and individual extension methods in delivering agroforestry technologies at Vi-Agroforestry project, Masaka district. Participatory Rural Appraisals (PRAs) tools including semi-structured questionnaires were administrated to 90 randomly selected farmers who had received extension services from the project. In addition, twelve project extension workers were interviewed. Data were analysed using SPSS computer package and descriptive analysis. A statistical t-test was carried out to assess the influence of group and individual extension methods on farmers’ adoption of agroforestry technologies. Group and individual methods were found to have varying degree of success on farmers’ implementation of agroforestry technologies (t = 3.55, p<0.05). In disseminating agroforestry technologies, group methods were found to be the most effective methods and hence most farmers preferred group methods. At the policy level, improving the quality of both group and individual extension methods is of paramount importance in order to address a variety of farmer characteristics in Uganda.
Keywords: Agroforestry technologies, extension methods, farmers, Uganda